The Influence of Discipline and Work Ethics, as well as Work Environment, on Employee Performance through Job Satisfaction as an Intervening Variable among Employees of the East Kutai Regional House of Representatives - Titin Ruliana; Andri Indrawati; Abdi Firdaus (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the impact of work discipline, work ethics, and work environment on job satisfaction, as well as their effect on employee performance among employees of the East Kutai Regency DPRD. The research employs a quantitative approach with a descriptive format, utilizing a saturated sampling technique on a population of 101 employees. Data were collected through fieldwork research and library research. The findings reveal that work discipline has a significant positive effect on job satisfaction, while work ethics shows a positive but insignificant effect. The work environment significantly enhances job satisfaction. Additionally, job satisfaction significantly influences performance, as do work discipline, work ethics, and work environment. Notably, work discipline positively impacts performance through job satisfaction, while work ethics has a positive but insignificant effect through job satisfaction. The study's limitations include the relatively small sample size and focus on a specific population, which may limit the generalizability of the results to broader contexts. Organizations should focus on improving work discipline and the work environment to enhance job satisfaction, ultimately boosting employee performance. This research contributes to understanding the relationships between work discipline, work ethics, work environment, job satisfaction, and employee performance, particularly within the context of local government institutions in Indonesia.